Os 'dilemas' do professor de ensino religioso nos anos iniciais do ensino fundamental entre a prática pedagógica, a legislação e os sete saberes de Edgar Morin. - Santos, Vandecarmen Rodrigues dos (2020)
The present dissertation, related to the research line, Campo Religioso Brasileiro, intends to analyze the “dilemmas” of the Religious Education teacher in the early years of Elementary Education, between the pedagogical practice, the Legislation and the Seven Knowledge of Edgar Morin. Historically situating Religious Education in Brazil and in the Municipality of Cabo de Santo Agostinho and the performance of the teacher in accordance with current legislation, developed in the school context in the early years of Elementary Education, ensuring respect for cultural, ethical, religious diversity, contextualizing knowledge in an interdisciplinary view, in basic and citizen education (by LDBEN nº 9.394/96 and its modification in Law nº 9.475 / 1997). Models from different perspectives in the theoretical and methodological process consolidating Religious Education in the school curriculum in an innovative vision of transformation and valorization in the construction of establishing one's own identity. The methodological path was carried out through bibliographic, documentary and qualitative analysis involving the theoretical and historical research of ER. and the dilemmas in the teacher´s teacher training, finally, issues of reflection were raised in the pedagogical practice and the continuity of the pedagogical proposal of Religious Education in order to ensure that the students of the municipal public schools have access to religious knowledge produced by humanity, contributing to respect for diversity in our society.